1981
DOI: 10.1002/jcp.1041070214
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan synthesis and composition in human fibroblasts during in vitro cellular aging (IMR‐90)

Abstract: The synthesis and turnover of sulfate-labeled glycosaminoglycans(35S-GAGs) has been investigated in diploid human embryo fibroblasts during in vitro cellular aging. With progressive subcultivation, there was a decreased incorporation of Na2(35)SO4 into 35S-GAGs released to the medium, but not into those accumulated at the cell surface. The composition of 35S-GAGs found in extracellular medium, cell surface (removable by gentle proteolysis), and intracellular compartments of the culture after 48-hr labeling did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…It has been known that undifferentiated cells are small in size and very proliferative, but differentiated cells are large in size and arrest their cell cycle (4, 35). Changes in the activity of synthesis and secretion of extracellular components, collagen and fibronectin, with age are controversial among authors (11,19,25,27,37). The relationship between the extent of differentiation and the activity of synthesis of extracellular substances has not been examined yet in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that undifferentiated cells are small in size and very proliferative, but differentiated cells are large in size and arrest their cell cycle (4, 35). Changes in the activity of synthesis and secretion of extracellular components, collagen and fibronectin, with age are controversial among authors (11,19,25,27,37). The relationship between the extent of differentiation and the activity of synthesis of extracellular substances has not been examined yet in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the intracellular levels of heparan sulfate with antiproliferative activity, our observations are consistent with the presence of a large pool of minimally active heparan sulfate within the postconfluent SMCs and/or an accelerated destruction of mucopolysaccharide with growth inhibitory potency within the SMCs. In this regard, other investigators have observed that secreted and cell surface heparan sulfate are handled as separate metabolic pools in other cell types (29).…”
Section: Discussionmentioning
confidence: 99%
“…This is sustained by the observation that in other human fibroblasts, fibronectin production [24] and the secre tion of GAG [2,3] were also markedly re duced in cells that have been subjected to progressive subcultivation.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it seems that these stromal cells did not present the morphological and cellu lar patterns which characterize in vitro-aged cells [22,23]. Early passage human embryo lung fibroblasts behave in a similar fashion and do not show significant changes in cell characteristics until they reach 30 CPD [2],…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation